Hubungan Antara Family Belief Systems dan Tipe Pola Asuh Dengan Behaviour Problems Pada Anak Dengan Down Syndrome - Neneng Tati Sumiati (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
Children with Down Syndrome have limited cognitive-related ability and special fenotive behavior. In this study, special and prominent behavior problem on children with down syndrome, such as comprehending ability, limited attention, disobedience, impulsiveness, compulsiveness, social withdrawal, aggression, and passivity which are related to family belief systems and parenting style. Sample of this study are 16 parents of children with down syndrome who are members of Perkumpulan Orang Tua Anak Dengan Down Syndrome (POTADS), Jakarta. Sampling technique used in this study was nonprobability sampling, incidental sampling. Analysis of data used was nonparametric, using Wilcoxon Correlation Test, α=0.05. Result of this study indicates family belief system and parenting style are significantly negatively correlated. Nine of 16 respondents stated their children has problem on emotion aspect. This condition indicates how important it is to train them to control their emotion DOI: 10.15408/tazkiya.v20i2.9173